Tract Size in Percutaneous Nephrolithotomy (PCNL) : Does It Really Matter? (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background : Percutaneous Nephrolithotomy (PCNL) is the treatment of choice in removal of renal and proximal ureteral calculi. The primary goal of PCNL is to achieve stone free status while minimizing morbidity and complications. In recent years, the instruments used have been miniaturized in an effort to decrease morbidity associated with standard PCNL as well as increase the efficacy of stone removal. The aim of this study is to compare the safety and efficacy of PCNL using different tract size.Materials and methods: This hospital based prospective interventional study was conducted on patients with 1 to 4 cm renal stones who underwent PCNL either by Minior Standard PCNL technique in Chattogram Medical College Hospital and different private hospitals in Chittagong from July 2016 to June 2018. Patients aged above 12 years of age, irrespective of gender with normal renal function were evaluated to compare stone clearance, total operative time, need for blood transfusion, postoperative pain and other complications. Those who had previous history of open renal surgery, active urinary tract infection, renal malformation, uncorrected coagulopathy and morbid obesity were excluded.Results: A total of 64 patients were enrolled consecutively for PCNL who were divided equally into two groups randomly for minimally invasive PCNL (Mini- PCNL) and Standard PCNL. The average stone size in mini-PCNL group was 2.64 ± 0.94 cm and 2.776 ± 0.97 cm in standard-PCNL group. Mean tract size was 18.44 ± 1.32 F (16-20) and 26.7 ± 5 F (24-30) respectively. In mini-PCNL operative time was significantly longer than that of standard PCNL with 110.31 ± 21.77 vs 95.94 ± 19.82 min respectively. Conversely, there was an advantage of mini-PCNL over the standard one in terms of a significantly reduced hemoglobin drop (0.5 ± 0.25 vs. 0.8 ± 0.34) gram and hospital stay (2.13 ± 0.79 vs.3.38 ± 1.13 days) respectively though there was no statistical difference in terms of stone clearance rates between two groups (86.7% vs. 93.33%). There was no statistical difference in terms of Visual Analogue Scale (VAS) score (5.44 ± 1.5 vs.6.19 ± 1.65) for pain perception. The complication rate of mini-PCNL had no significant difference with that of standard PCNL (10% vs 13.6%). No statistical difference was recorded in terms of postoperative fever (³38oC) between two groups (2 in each group, 6.67%, p=1). Blood transfusion requirement was much less in mini PCNL group (10% vs. 33.33%).Conclusion: In addition to minimal bleeding and excellent stone clearance, mini- PCNL has several features for which it should be considered as an alternative or adjunct to standard PCNL, URS and ESWL. These include safe supra-costal puncture, excellent access to nearly all calyces and upper ureter, less hospital stay and suitable for large stones also. Future studies should continue to refine methods to assess complexity and safety and to determine consensus on the use of mini- PCNL.Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 18-22